Benthic Infauna in the Shallow-Water Hydrothermal System of Banderas Bay, Mexico: A Two-Period Comparison - María Carolina Rodríguez-Uribe; Rosa María Chávez-Dagostino; Patricia Salazar-Silva; Jani Jarquín-González; Alma Rosa Raymundo-Huizar; Fátima Maciel Carrillo-González (Diversity, 2025)
At a depth of approximately 9 m off the coast of Banderas Bay, hydrothermal activity occurs through various seabed vents, discharging liquids and gases that reach temperatures of up to 89 °C and pH values lower than the surrounding seawater. This study examines the composition of the benthic infauna inhabiting the sediments of this hydrothermal system in two time periods: November 2017 (previously reported) and September 2023 (recorded for this study). In total, for both samplings, we identified 17 benthic infaunal groups—amphipods, isopods, cumaceans, tanaidaceans, crabs, shrimps, copepods, snails, limpets, caecids, chitons, bivalves, scaphopods, polychaetes, amphioxus, ophiuroids, and bryozoans—belonging to these ten taxonomic classes: Malacostraca, Maxillopoda, Gastropoda, Polyplacophora, Bivalvia, Scaphopoda, Polychaeta, Leptocardii, Ophiuroidea, and Stenolaemata. Additionally, we identified galleries of polychaetes, vermetids, and peracarids. Despite the stressful hydrothermal conditions, statistical analyses of both sampling campaigns revealed no significant differences in abundance, highlighting the potential persistence and adaptability of benthic communities in hydrothermally influenced habitats.